Movement abnormalities and psychotic-like experiences in childhood: markers of developing schizophrenia? - Macmanus, Deirdre; Hodgins, Sheilagh (Psychological medicine, 2012)
BackgroundBoth involuntary dyskinetic movements and psychotic-like experiences (PLEs) are reported to be antecedents of schizophrenia that may reflect dysfunctional dopaminergic activity in the striatum. The present study compared dyskinetic movement abnormalities displayed by children with multiple antecedents of schizophrenia (ASz), including speech and/or motor developmental lags or problems, internalising/externalising problems in the clinical range, and PLEs, with those displayed by children with no antecedents (noASz).MethodThe sample included 21 ASz and 31 noASz children, aged 9-12 years old. None had taken psychotropic medication or had relatives with psychosis. The antecedents of schizophrenia were assessed using questionnaires completed by children and caregivers. A trained rater, blind to group status, coded dyskinetic movement abnormalities using a validated tool from videotapes of interviews with the children.ResultsASz children reported, on average, ‘certain experience’ of 2.5 PLEs, while noASz children, by definition, reported none. The ASz children, as compared with noASz children, displayed significantly more dyskinetic movement abnormalities in total, and in the facial and the upper-body regions, after controlling for sex and age. Receiver operator characteristics analyses yielded high area under the curve values for the total score (0.94), facial score (0.91) and upper-body score (0.86), indicating that these scores distinguished between the ASz and noASz children with great accuracy.ConclusionsBrief questionnaires identified children with multiple antecedents of schizophrenia who displayed significantly more involuntary dyskinetic movement abnormalities than children without antecedents. The presence of PLEs and dyskinesias could reflect early disruption of striatal dopamine circuits.
Published online: 11 July 2011
Gesehen am 31.07.2018